Differential Impacts of 1.5 and 2 °C Warming on Extreme Events Over China Using Statistically Downscaled and Bias‐Corrected CESM Low‐Warming Experiment. Issue 18 (26th September 2018) - Yang, Yi; Tang, Jianping; Wang, Shuyu; Liu, Gang
Abstract: Using statistically downscaled and bias‐corrected CESM (Community Earth System Model) 11‐member ensemble, we investigate the changes in precipitation and temperature extremes over China in 1.5 and 2 °C warmer climates. Most regions will experience a significant increase in wet extreme indices accompanied by fewer consecutive dry days under both warming targets. An additional 0.5 °C warming may result in stronger increases in wet extreme indices over most subregions and weak decreases over North China, although the grid point‐level changes between the two scenarios are mostly nonsignificant. A robust increase in extreme high‐temperature events and TNn (the coldest night) is found across China at a 2 °C relative to 1.5 °C scenario. Compared to a 2 °C world, a 0.5 °C less warming avoids 32–34% of the increases in the frequency and intensity of temperature extremes in China, particularly over Northeast China. Plain Language Summary: Extreme precipitation and temperature events have serious impacts on natural ecosystems and human health over China. It is therefore crucial to assess how the extreme events may change in China under different warming levels. A set of simulations for the 1.5 and 2 °C targets are applied to investigate the changes in climate extremes over China and the benefits of limiting warming to 1.5 °C instead of 2 °C. Although the differences between the two warming levels are nonsignificant, a general wetting condition is expected for most areas when shifting from the 1.5 to 2 °C scenario. If a 1.5 °C scenario is followed, there will be a substantial reduction in the increases in hot extremes relative to 2 °C warming across the domain. The reduced impacts on the frequency and intensity of temperature extremes are estimated to be about 33% with 0.5 °C less global warming. Key Points: Changes in extreme events over China in 1.5 and 2 °C warmer climates using statistically downscaled and bias‐corrected CESM data A wetting tendency is expected for precipitation extremes due to an additional 0.5 °C warming although the changes are mostly nonsignificant Limiting warming to 1.5 °C relative to 2 °C has the benefits of avoiding the increases in the frequency and intensity of hot extremes